EFFECTS OF CAULERPA LENTILLIFERA SIMPLISIA ADMINISTRATION ON GASTRIC AND SMALL INTESTINAL HISTOPATHOLOGY IN WHITE RATS POST PARACETAMOL INDUCTION - Baiq Melisa Ulandari Utami; Ida Bagus Oka Winaya; Yudha Yaksa Crada Yoga Arum Raharjo; Samsuri; I Made Merdana (Buletin Veteriner Udayana, 2025)
Caulerpa lentillifera is known as sea grapes macroalgae or sea grapes which have benefits as antioxidants. Paracetamol is a drug that is sold freely and many people abuse it. Abuse of paracetamol can cause negative impacts on various organs, one of which is the stomach and small intestine. The purpose of this study was to determine the effect of administering Caulerpa lentillifera on the histopathology of the gastric and small intestine of white mice given paracetamol in high doses. This study used a completely randomized design method. A sample of 25 male white mice was divided into 5 treatment groups, namely negative control (P0) or no treatment, positive control (P1) was only given paracetamol 250 mg/kgBB, P2 was given paracetamol 250 mg/kgBB and sea grapes 10 g/kgBB, P3 was given paracetamol 250 mg/kgBB and sea grapes 15 g/kgBB, and P4 was given paracetamol 250 mg/kgBB and sea grapes 20 g/kgBB. Treatment was given for 14 days, then necropsied. Samples of gastric and small intestine tissue were made into histopathology preparations using hematoxylin eosin (HE) staining. The variables examined in the gastric were gastric mucosal damage. While the variables examined in the small intestine included bleeding lesions and necrosis. Data were analyzed using the Kruskal Wallis Test followed by the Mann-Whitney test and described descriptively. The results showed that in gastric mucosal damage, small intestine necrosis, and small intestine bleeding showed that there was a difference (P<0.05) between groups. There was a process of improvement in the histopathology of the gastric and small intestine of white rats given Caulerpa lentillifera in gastric mucosal damage, small intestine necrosis, and small intestine bleeding. Based on the results of the study, it can be concluded that sea grapes with doses of 15 g/kgBB and 20 g/kgBB can minimize gastric mucosal damage. While a dose of 20 g/kgBB can minimize small intestine damage in necrosis and hemorrhage lesions